Myelodysplastic syndromes without peripheral monocytosis but with evidence of marrow monocytosis share clinical and molecular characteristics with CMML. (February 2018) - Schuler, E.; Frank, F.; Hildebrandt, B.; Betz, B.; Strupp, C.; Rudelius, M.; Aul, C.; Schroeder, T.; Gattermann, N.; Haas, R.; Germing, U.
Highlights: MDS patients with monocytic marrow proliferation have a more CMML-like phenotyp. MDS patients with monocytic marrow proliferation have a more CMML-like genotyp. MDS patients with monocytic marrow proliferation develop CMML more often. MDS patients with marrow monocytosis could potentially be very early stages of CMML. Abstract: MDS patients may present with monocytic marrow proliferation not fulfilling criteria for CMML. We analyzed MDS patients with or without a marrow monocytic proliferation by following up the amount of monocytic proliferation and characterizing their molecular profile. 315 MDS patients of Duesseldorf MDS registry were divided into two groups: A) 183 patients with monocytic esterase positive cells in marrow and monocytes between 101 and 900/μl in blood and B) 132 patients without monocytic esterase positive cells in marrow and monocytes in blood ≤100/μl. Twenty patients of each group were screened with regard to ASXL1, TET2, RUNX1, SETBP1, NRAS, and SRSF2 using Illumina myeloid panel. Group A patients were older, had significantly higher WBC, hemoglobin levels, neutrophils and platelets. CMML evolution rates were 4.9% and 1.5%, respectively (p = n.s.). TET2, NRAS and SRFS2 mutation frequencies were higher in group A and four patients had coexisting TET2 and SRFS2 mutation, which was shown to be characteristic but not specific for CMML. MDS patients with marrow monocytic proliferation have a more CMML-like pheno- and genotype and develop CMML more often. Those patients could potentially be very early stages of CMML or represent a CMML-like myeloid neoplasma with marrow adherence of the monocytic cell population.